Growth and physiological characteristics of Acacia species in a progeny trial - Senin, Abdul Latib (2016)
Acacia has introduced in Malaysia since 1932, as a shade tree, soil erosion control and widely planted in the tropics area. Acacia has introduced as a plantation species since 1978, with a focused on lumber production in the short term rotation. The objective of this study was to increase the knowledge about the best of Acacia from four species in term of the regions, provenances, progeny, and physiological characteristics. A field trial was established at Kampung Aur Gading, Kuala Lipis, Pahang, by using a completely randomized block design (RCBD) with four replications from 16 provenances comprising 410 families originated from PNG and QLD region. In this study, significant differences at p< 0.05 were observed between regions, provenances, and species for height, diameter at breast height, and survival. Among the four species, A. mangium found to be the most outstanding with its potential provenance from Bensbach WP (PNG) and SW of Boset WP (PNG). Meanwhile, A. aulacocarpa was better in the stem form, i.e., the second ranking behind A. mangium, but uppermost in class two. In another study of A. aulacocarpa from four provenances and twenty progenies, significant difference at p<0.05 for height, dbh and stem form. Arufi East Morehead WP and West Morehead provenances from PNG has better performance in terms of height, dbh, and survival compared with QLD. The best progenies in terms of height and survival rate were from progeny AR 000011 and BVG 00861 while the progeny BVG 00859 was the best in terms of Dbh. However, progeny GB 100 is the poorest. The gas exchange attributes of A. aulacocarpa species confirmed that the effect of different season influenced on the tree growth. The leaf area ratio and crown width also examined and the measurements were performed in dry and wet seasons. The results indicated that all gas exchange parameters exhibited higher rates in PNG provenances compared to QLD provenances, where W. Morehead outperformed the others. The progeny (BVG 00861) had the best overall physiological characteristics while the progeny (BVG 00860) had the best outcomes in the dry season while the progeny BVG 00859 performed best in the wet season. These findings clearly indicated that the differences in genotype, regions, provenances, and progeny contribute to different growth. The season changes, environmental conditions, and geographical location were also influenced the internal physiological characteristics of trees and these factors play a significant part in the growth of a tree.